2022
DOI: 10.1055/a-1828-2479
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Evaluation of ACE2 and LOX Inhibitory Activity of Origanum Essential Oils and Carvacrol

Abstract: Origanum spp. are used both for culinary purposes and for their biological activities. In this study, commercially Origanum majorana, O. minutiflorum, O. vulgare, and O. onites essential oils, and their prominent constituent carvacrol was evaluated for their in vitro and in silico angiotensin-converting enzyme 2 (ACE2) and lipoxygenase (LOX) enzyme inhibitory potentials. The essential oils were analysed by GC-FID and GC/MS, where carvacrol was identified as the major component (62–81%), confirming the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Ligand–protein interaction analysis shows carvacrol interacting with Glu802 and Ala1079 through HB and also forms other hydrophobic interactions with Phe914, Phe1009, and Ala1078 ( Figure 5 ). These results are in line with previously reported studies that highlighted the anti-lipoxygenase activity of essential oils due to their carvacrol and para -cymene content or the anti-lipoxygenase activity of carvacrol alone [ 102 , 103 , 104 , 105 ].…”
Section: Results Discussionsupporting
confidence: 93%
“…Ligand–protein interaction analysis shows carvacrol interacting with Glu802 and Ala1079 through HB and also forms other hydrophobic interactions with Phe914, Phe1009, and Ala1078 ( Figure 5 ). These results are in line with previously reported studies that highlighted the anti-lipoxygenase activity of essential oils due to their carvacrol and para -cymene content or the anti-lipoxygenase activity of carvacrol alone [ 102 , 103 , 104 , 105 ].…”
Section: Results Discussionsupporting
confidence: 93%
“…Essential oils and their main components have lipophilic properties, and some studies show that SARS-CoV-2 virus membrane integrity is disrupted and they have the potential to penetrate the membrane due to such structural features. , In a previous study by our group, it was demonstrated that linalool inhibited the ACE2 enzyme also by docking . Essential oils and their volatile major components also disrupt viral replication, benefiting the host respiratory system through mucus lysis and bronchodilation .…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 21 In a previous study by our group, it was demonstrated that linalool inhibited the ACE2 enzyme also by docking. 22 Essential oils and their volatile major components also disrupt viral replication, benefiting the host respiratory system through mucus lysis and bronchodilation. 23 The major compound linalool of Lavandula sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative retention times (RRTs) of the essential oils were compared to those of authentic samples or their relative retention index (RRI). Computer matching against commercial (Wiley GC/MS Library, MassFinder Software 4.0) and in-house "Başer Library of Essential Oil Constituents" databases built up by genuine compounds and components of known oils was used for identification as previously reported [41].…”
Section: Gas Chromatography-flame Ionization Detection and Gas Chroma...mentioning
confidence: 99%